Topical treatment of psoriasis: questionnaire results on topical therapy accessibility and influence of body surface area on usage. (19th April 2017) - Iversen, L.; Lange, M.M.; Bissonette, R.; Carvalho, A.V.E.; van de Kerkhof, P.C.; Kirby, B.; Kleyn, C.E.; Lynde, C.W.; van der Walt, J.M.; Wu, J.J.
Abstract: Background: Topical treatment of mild to moderate psoriasis is first‐line treatment and exhibits varying degrees of success across patient groups. Key factors influencing treatment success are physician topical treatment choice (high efficacy, low adverse events) and strict patient adherence. Currently, no formalized, international consensus guidelines exist to direct optimal topical treatment, although many countries have national guidelines. Objective: To describe and analyse cross‐regional variations in the use and access of psoriasis topical therapies. Methods: The study was conducted as an observational cross‐sectional study. A survey was distributed to dermatologists from the International Psoriasis Council (IPC) to assess topical therapy accessibility in 26 countries and to understand how body surface area (BSA) categories guide clinical decisions on topical use. Results: Variation in the availability of tars, topical retinoids, dithranol and balneotherapy was reported. The vast majority of respondents (100% and 88.4%) used topical therapy as first‐line monotherapy in situations with BSA < 3% and BSA between 3% and 10%, respectively. However, with disease severity increasing to BSA > 10%, the number of respondents who prescribe topical therapy decreased considerably. In addition, combination therapy of a topical drug and a systemic drug was frequently reported when BSA measured >10%. Conclusion: This physician survey provides new evidence on topical access and the influence of disease severity on topical usage in an effort to improve treatment strategies on a global level.